Pemberdayaan Masyarakat Kelurahan Suka Maju Melalui Pelatihan Pembuatan Sabun Kebutuhan Rumah Tangga - Munawarah; Keumala Hayati; Mas Intan Purba; Wenny Anggeresia Ginting (Universitas Lancang Kuning, 2020)
Soap is a necessity in the household that is continuously used, so the costs incurred are also quite large. The purpose of this washing soap training is to provide public knowledge especially housewives in Suka Maju Kelurahan in making soaps such as dishwashing soap, floor cleaning soap, detergent, softener and fragrances of clothes that are often used for daily needs, to reduce expenses routinely. This activity also encourages creativity and interest in trying to make them get an extra income. The team worked closely with the community empowerment agency Suka Maju Village,through the village funding program to create an independent,having soft skills community to be able to improve the economy. Activities that lasted for two days showed that public is enthusiastic and understands the workings of making products, as well as succeeding in making products well. T- test results also showed a sig value of 0.003 meaning that there were differences between before the activity took place and after the training.